Sleep disturbance linked to suicidal ideation in postural orthostatic tachycardia syndrome - Pederson CL (Dove Medical Press, 2017)
Cathy Lynn Pederson,1 Jill Blettner Brook2 1Department of Biology, Wittenberg University, Springfield, OH, USA; 2PatientsCount, Anchorage, AK, USA Objective: We investigated the prevalence of suicidal ideation in relationship with symptoms of sleep disruption in people with postural orthostatic tachycardia syndrome (POTS). Methods: Online surveys (including the Pittsburgh Sleep Quality Index and the Suicide Behaviors Questionnaire – Revised) were completed by 705 POTS patients and 170 non-POTS controls. Results: Poor sleep quality was reported in 98.4% of POTS patients with a calculated subjective sleep efficiency of 65.4%. The POTS group’s sleep efficiency was significantly lower (t[873]= –11.32; p<0.001) and sleep disturbances because of pain were significantly higher (t[873]=15.36; p<0.001) than controls. Chi-square testing showed a larger proportion of individuals at high-risk for suicide among POTS patients than controls (χ2 [1, n=875]=55.6; p<0.001). Multiple linear regression analysis showed that sleep scores (β=0.23, p<0.001), age (β=–0.03, p<0.001), and illness with POTS (β=0.68, p=0.05) were significantly associated with suicide ideation scores (F[4, 870]=38.34, p<0.001). This model explained 15% of variance (R2=0.15) in suicidal ideation scores. Conclusion: Patients with POTS may suffer from increased sleep disturbance and suicidal ideation compared with the general population. Treatment to improve sleep efficiency and sleep quality is an important step toward better quality of life for POTS patients. Keywords: postural orthostatic tachycardia syndrome, POTS, sleep, insomnia, suicidal ideation, suicide